ALUMNI MANAGEMENT AT ISLAMIC BOARDING SCHOOL (CASE STUDY AT PONDOK PESANTREN NURUL JADID) - A. Fathorrazi; Ainur Rifqi (Faculty of Education Universitas Negeri Malang, 2017)
The aim of this research is to describe: (1) the profile of alumni address and profession, (2) alumni management including planning, organizing, alumni development, empowerment, and evaluation, (3) communication for the network building of the alumni association at Pondok Pesantren Nurul Jadid. This study was qualitative in nature. This study found: (1) location, vision, institute, and Pesantren facilities influenced the deployment of alumni jobs and professions; (2) management steps include: preparing alumni candidate, encoding, programming, developing alumni competencies, empowering alumni, and evaluating; (3) network building of alumni is built through organisations and individuals Keywords: alumni, alumni mangement, pondok pesantren